2013
DOI: 10.1158/0008-5472.sabcs13-s3-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S3-03: Randomized trial of exercise vs. usual care on aromatase inhibitor-associated arthralgias in women with breast cancer: The hormones and physical exercise (HOPE) study

Abstract: PURPOSE: Arthralgias occur in up to 50% of women with breast cancer treated with adjuvant aromatase inhibitors (AIs), and are one of the most common reasons for poor adherence to therapy. We examined whether a year-long exercise program improves arthralgias in breast cancer survivors taking AIs. METHODS: Postmenopausal women diagnosed with hormone receptor-positive breast cancer were identified via the Connecticut Tumor Registry. Women who were taking an AI for at least 6-months and reported ≥ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…In our pilot study conducted among survivors age 65 or older, we found a 32% decrease in joint stiffness (Cohen’s d effect size=0.56; p=0.07) between baseline and 6 weeks (end of intervention), and an increase from 21% to 50% in the proportion of survivors who walked the targeted amount of 150 minutes per week (p<0.001) [14]. More recently, findings from a recently published RCT of breast cancer survivors on AI therapy included a 29% decrease in worst pain scores among women assigned to a 12-month exercise program as compared to a 3% increase in worst pain in the usual care control group (p<0.001) [41]. The exercise group also experienced significantly decreased pain severity and pain interference compared to the usual care group (p<0.001) [41].…”
Section: Discussionmentioning
confidence: 99%
“…In our pilot study conducted among survivors age 65 or older, we found a 32% decrease in joint stiffness (Cohen’s d effect size=0.56; p=0.07) between baseline and 6 weeks (end of intervention), and an increase from 21% to 50% in the proportion of survivors who walked the targeted amount of 150 minutes per week (p<0.001) [14]. More recently, findings from a recently published RCT of breast cancer survivors on AI therapy included a 29% decrease in worst pain scores among women assigned to a 12-month exercise program as compared to a 3% increase in worst pain in the usual care control group (p<0.001) [41]. The exercise group also experienced significantly decreased pain severity and pain interference compared to the usual care group (p<0.001) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent hormones and physical exercise (HOPE) study, which randomised AI users to exercise or usual care, showed that exercise intervention led to clinical meaningful improvements in AIMSS [36].…”
Section: Discussionmentioning
confidence: 99%
“…Improving or preserving muscle strength is important because of increased resilience to musculoskeletal injury and muscular strength, playing a fundamental role in reducing joint pain and physical limitation, thus increasing QoL [32,33]. These results are complemented with a significant improvement in affected shoulder range of motion.…”
Section: Discussionmentioning
confidence: 99%